The Integration of Social-Emotional Learning in Arabic Textbooks: A Content Analysis Based on the CASEL Framework in the Al-ʿArabiyyah li al-Ḥayāh Series: English - Hasan Syukur; M. Khozinul Asror; Darul Jalal; Wahyu Putra Pratama; Faqih (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to analyze the representation and balance of Social-Emotional Learning (SEL) skills in the Al-ʿArabiyyah li al-Ḥayāh textbook series, volumes 1–4, used in the Special Arabic Language Program (PKPBA) at UIN Maulana Malik Ibrahim Malang. Using a qualitative approach with a deductive content analysis method based on the CASEL framework, this study examined the texts, dialogues, and exercises in all four volumes to identify the representation of five SEL competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The analysis identified 184 units of SEL data with an unbalanced distribution: relationship skills dominated (44 findings; 23.9%), followed by responsible decision-making (41; 22.3%), self-awareness (36; 19.6%), self-management (32; 17.4%), and social awareness as the lowest (31; 16.8%). Across volumes, Volume 2 had the highest concentration (71 findings; 38.6%), indicating a pattern of instructional clustering. An evaluation using the SAFE criteria (Sequenced, Active, Focused, Explicit) showed that SEL integration remains implicit, is not sequenced within the curriculum, and does not yet meet the standards for effective SEL design. These findings have important implications for the development of more holistic, balanced, and social-emotional competency-based Arabic teaching materials in Indonesian Islamic higher education.